Physical Literacy on Physical Activity Levels and Physical Fitness Among Adolescents - Fauzi Maulana; Dedi Supriadi; Vicki Ahmad Karisman (Universitas Negeri Semarang, 2026)
Low levels of physical activity among adolescents remain a major global public health concern. One of the factors that may influence adolescents' engagement in physical activity and their physical fitness is physical literacy. Therefore, this study aimed to examine the effect of physical literacy on the level of physical activity and physical fitness among adolescents. This research employed a quantitative approach with a cross-sectional explanatory design. The participants of this study were 132 high school students aged 15–17 years from Advent High School Bandung using total sampling. Data were collected using the Perceived Physical Literacy Instrument (PPLI) to measure physical literacy, the International Physical Activity Questionnaire (IPAQ) to measure physical activity, and the Indonesian Physical Fitness Test (TKJI) to measure physical fitness. Data analysis was conducted using descriptive statistics, Pearson correlation, and simple linear regression analysis with the assistance of SPSS version 25. The results showed that physical literacy had a significant positive relationship with physical activity (r = .818, p < .001) and physical fitness (r = .904, p < .001). Regression analysis indicated that physical literacy significantly predicted physical activity (β = .818, t = 16.209, p < .001) with a coefficient of determination of R² = .669. In addition, physical literacy also significantly predicted physical fitness (β = .904, t = 24.178, p < .001) with a coefficient of determination of R² = .818. These findings indicate that adolescents with higher levels of physical literacy tend to have higher levels of physical activity and better physical fitness. Therefore, the development of physical literacy through physical education programs is essential to promote active lifestyles and improve physical fitness among adolescents.